The Asymmetric Impact of Oil Price Shocks on Kazakhstan Macroeconomic Dynamics: A Structural Vector Autoregression Approach - Köse, Nezir; Baimaganbetov, Sabit (International Journal of Energy Economics and Policy, 2015)
This paper assesses empirically the asymmetric effects of real oil price shocks on the industrial production, real exchange rate and inflation in Kazakhstan for the monthly period 2000-2013 by using a Structural VAR model. Structural VAR analysis is carried out using the scaled model. The empirical findings show that the negative oil price shocks have a larger impact on Kazakhstan economic performance. Keywords: Oil price shocks, structural VAR, asymmetric effects, Kazakhstan. JEL classification: C22; C32; Q43